A separable cohesive element for modelling coupled failure in laminated composite materials. (April 2018) - Lu, X.; Chen, B.Y.; Tan, V.B.C.; Tay, T.E.
Abstract: A three-dimensional separable cohesive element (SCE) is proposed to enable the modelling of interaction between matrix cracking and interfacial delamination in laminated fibre-reinforced composite materials. It is demonstrated that traditional cohesive elements are incapable of modelling the coupled failure mechanisms accurately if partitioning is not allowed. The SCE may be partitioned according to the configuration and geometry of matrix cracks in adjacent plies, thus maintaining appropriate connection between plies. Physically, the original interface is split and new interfaces are formed to bond the homologous cracked solids during fracturing process. The stress concentration induced by matrix cracks and the load transfer from cracked solid elements to interface cohesive element are effectively modelled. A comprehensive set of cases of multiple matrix crack configurations from plies of different fiber angles is considered. The proposed SCE is applied to model progressive failure in composite laminates and the results are found to agree with experiments.